Effects of participation intensity on agricultural commercialization level among sweet potato farmers in Kwara and Osun States, Nigeria - Oyebamiji, Isaac Ttunde; Togun, Oladele Michael; Adedoyin, Elisa Aderonke; Agbana, Olugbenga; Shittu, Moshod Bola; Kolawole, Juliet Yemisi (International Journal of Sustainable Agricultural Research, 2024)
This study examined the effects of participation intensity on agricultural commercialization of sweet potatoes in Kwara and Osun States, Nigeria. Sweet potato is particularly a suitable food security crop as it produces a high yield in a short growing season even under low rainfall. A multistage sampling technique was used to select 485 sweet potato farmers. An interview guide was used to obtain primary data, which were analysed using descriptive and double hurdle Craggit regression models. The results revealed that majority of the respondents were male (86% and 87.6%) in both Kwara and Osun states, while the mean ages were 42 and 43 years, respectively. The results further showed that sweet potato intensity of participation in commercialization was significantly determined by gender, quantity consumed, and transaction cost of the crop in Kwara State (p<0.1, p<0.01, and p<0.05), respectively. However, for Osun state, it was significantly determined by age, gender, education, quantity consumed, and cooperative membership (p<0.1, p<0.1, p<0.01, p<0.01 and p<0.01), respectively. The study concluded that agricultural commercialization level of sweet potato was directly influenced by many factors in the study areas. It is therefore recommended that farmers should be assisted in lowering their transaction costs, particularly in terms of transportation costs. Cooperative membership performance should be enhanced positively for farmers through seminars, symposiums, and training.